2015
DOI: 10.1007/s12011-015-0313-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic and Inorganic Forms of Manganese, Zinc, Copper, and Chromium on Bioavailability of These Minerals and Calcium in Late-Phase Laying Hens

Abstract: In the present study, the effects of dietary supplementation of organic and inorganic Mn, Zn, Cu, and Cr mixtures using two different levels (80, 60, 5, and 0.15 mg/kg and 40, 30, 2.5, and 0.07 mg/kg, respectively) on the bioavailability of these trace minerals and Ca in late-phase laying hens were evaluated. Three hundred and sixty laying hens (Barred Rock) at 50 weeks of age were used, and the duration of study was 16 weeks. Each of the four dietary regimes was randomly assigned to six replicates, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 31 publications
(65 reference statements)
7
33
3
2
Order By: Relevance
“…Similarly, plasma total protein was increased with Zn dietary supplementation in broiler (Feng et al, 2010). Higher calcium and phosphorus levels in broiler blood serum fed on organic or nano zinc are in agreement with those obtained by Yenice et al (2015) indicated that using the organic form of the trace mineral mixture significantly increased the serum Ca concentration compared with the inorganic form. However, Güçlü and İşcan (2004) reported that organic Mn and Zn supplementation of laying hen diets did not affect serum Ca, P, and Mg concentrations.…”
Section: 6antioxidant Enzyme Activitysupporting
confidence: 84%
“…Similarly, plasma total protein was increased with Zn dietary supplementation in broiler (Feng et al, 2010). Higher calcium and phosphorus levels in broiler blood serum fed on organic or nano zinc are in agreement with those obtained by Yenice et al (2015) indicated that using the organic form of the trace mineral mixture significantly increased the serum Ca concentration compared with the inorganic form. However, Güçlü and İşcan (2004) reported that organic Mn and Zn supplementation of laying hen diets did not affect serum Ca, P, and Mg concentrations.…”
Section: 6antioxidant Enzyme Activitysupporting
confidence: 84%
“…Data obtained from our study showed that MHA-Ca supplementation significantly improved the eggshell thickness, relative eggshell weight and eggshell strength with. The reason may because Ca is the first restrictive factor in eggshell formation [18], and the main source of Ca in eggshell are obtained from intestinal absorption and bone Ca mobilization [19]. Thus, the explanation why MHA-Ca promoted the eggshell quality significantly may because MHA-Ca provided extra Ca source.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that organic zinc source, such as ZnGly, had a significantly higher bioavailability than zinc sulfate has been reported by others (Cao et al 2000;Rider et al 2010). Yenice et al (2015) have shown that organic Zn increases the bioavailability of Zn compared with inorganic sources. Although the exact mechanism for the increased bioavailability of ZnPOS was unclear and still needs further study, several hypotheses have been proposed for the higher bioavailability of organic minerals than inorganic minerals.…”
Section: Discussionmentioning
confidence: 68%